Prioritizing Urban Sustainability Indicators: A Participatory Analysis Based on the Sustainable Cities Program Methodology - Silva, Maria Lucineide Gomes da; Cândido, Gesinaldo Ataíde; Lima, Eduardo Rodrigues Viana de (National Journal of City Management, 2025)
Objective – This study aims to prioritize the most relevant urban sustainability indicators that best highlight the unique characteristics of an important urban agglomeration in the state of Ceará, based on a participatory process. Methodology – In methodological terms, this study is an applied, exploratory, and descriptive research project. To achieve its objective, it adopted a methodology based on the Sustainable Cities Program (PCS). Initially, the indicators most relevant to the urban context of the region were selected. Next, a public consultation was held with local residents of legal age who had completed elementary school, reducing the set to 20 indicators with greater homogeneity in the responses. These were then submitted to analysis by social actors directly linked to municipal management and the indicators, using the Mudge Diagram tool to determine the order of importance of the indicators. Originality/Relevance – The study is part of the theoretical debate on the importance of integrating indicators validated by society and urban management tools in medium-sized cities in developing countries. It stands out for its emphasis on participatory methodologies and the scarcity of studies that link sustainable indicators to the reality of municipalities in the northeastern interior. Results – The results point to the prioritization of social indicators, with an emphasis on health, education, and urban infrastructure, highlighting the main areas of attention for sustainable development in CRAJUBAR. Theoretical/Methodological Contributions – The use of the Mudge Diagram proved to be an effective tool for organizing and prioritizing indicators based on the perceptions of social actors, reinforcing the viability of participatory methods in the context of local urban management. Social and Environmental Contributions – The study offers relevant insights for public policies that are more responsive to the real needs of the population, contributing to the construction of more inclusive, healthy, and environmentally sustainable cities. KEYWORDS: Urban. Cities. Sustainability. Indicators.